The Problems of Homeschooling Arabic Learning in Sidoarjo - Vita Ratnasari; Najih Anwar (Universitas Muhammadiyah Sidoarjo, 2022)
The Problems of Learning Arabic in the Khoiru Ummah Homeschooling Group 12 Throughout. Formulation of the problem; 1) What are the problems of learning Arabic in the Khoiru Ummah 12 Homeschooling Group? 2) How to solve the problems of learning Arabic in the Khoiru Ummah 12 Homeschooling Group? The research method used by the researcher is a descriptive qualitative approach. The results of the study: 1) Arabic learning problems a) linguistic problems, namely i) phonological aspects ii) syntactic aspects iii) semantic aspects. b) non-linguistic problems, namely i) in terms of process ii) in terms of results. 2) Solutions to the problems of learning Arabic a) solutions to linguistic problems b) solutions to non-linguistic problems.